2009
DOI: 10.1016/j.biocel.2008.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically constrained α-helical peptide inhibits replication of HIV-1 resistant to enfuvirtide

Abstract: Alpha-helical peptides, such as T-20 (enfuvirtide) and C34, derived from the gp41 carboxyl-terminal heptad repeat (C-HR) of HIV-1, inhibit membrane fusion of HIV-1 and the target cells. Although T-20 effectively suppresses the replication of multi-drug resistant HIV variants both in vitro and in vivo, prolonged therapy with T-20 induces emergence of T-20 resistant variants. In order to suppress the emergence of such resistant variants, we introduced charged and hydrophilic amino acids, glutamic acid (E) and ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 48 publications
2
55
0
Order By: Relevance
“…Moreover, this strategy should not result in more adverse effect than those that might be obtained during use of the original peptide or oligonucleotide reagents. Recently we (6,30,31) and others (5) reported that hydrophilic amino FIGURE 4. Replication kinetics of HIV-1 S138X variants (X, any natural amino acid).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this strategy should not result in more adverse effect than those that might be obtained during use of the original peptide or oligonucleotide reagents. Recently we (6,30,31) and others (5) reported that hydrophilic amino FIGURE 4. Replication kinetics of HIV-1 S138X variants (X, any natural amino acid).…”
Section: Discussionmentioning
confidence: 99%
“…acid substitutions stabilized the ␣-helix of C-HR peptides and increased their binding affinity to N-HR, thus providing potent anti-HIV activity. This property may be one of the key attributes of the recently developed potent peptide inhibitors, SC34EK (6,30), T-20EK (31), or T-2429 (5), that have been reported to efficiently inhibit T-20 resistant variants. However, the S138A substitution on T-20 in the present study had little effect on the random coil structure, as judged by CD (data not shown), indicating that T-20 S138A increases its binding affinity not by simply enhancing the ␣-helicity of this region (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) (17). SC34EK, which has unidirectional EK motifs, demonstrated a 5-fold enhanced activity compared with the original C34 (15,17). We demonstrated that the ␣-helical structure was stabilized by electrostatic in-* This work was supported, in whole or in part, by National Institutes of Health Grants AI076119, AI074389, and AI079801 (to S. G. S.), in part by a grant for Promotion of AIDS Research from the Ministry of Health and Welfare of Japan (to E. N. K. and M. M.), a grant for Research on Health Science Focusing on Drug Innovation from the Japan Health Science Foundation (to E. N. K. and M. M.), and a grant from the Ministry of Education, Culture, Sports, Science and Technology of Japan (to E. N. K.).…”
mentioning
confidence: 94%
“…These inhibitors include tifuvirtide (T-1249) (12), T-2410 (13), and sifuvirtide (14), which are able to suppress T-20-resistant variants. We have developed electrostatically constrained fusion inhibitors, SC34 and SC34EK, which inhibit replication of T-20-resistant HIV-1 (15). SC34 was designed to be more soluble and have enhanced ␣-helicity, by engineering electrostatic interactions between glutamic acid and lysine substitutions at i and iϩ4 positions in the solvent-interacting site (EK motif) (16) of the parental C-HRderived C34 peptide ( Fig.…”
mentioning
confidence: 99%